Beating Rate Variability of Isolated Mammal Sinoatrial Node Tissue: Insight Into Its Contribution to Heart Rate Variability - Shemla, Ori; Tsutsui, Kenta; Behar, Joachim A.; Yaniv, Yael (Frontiers in Neuroscience, 2021)
Background: Because of the complexity of the interaction between the internal pacemaker mechanisms, cell interconnected signals and interaction with other body systems, study of the role of individual systems must be performed under in vivo and ex vivo conditions. The in-situ approach is valuable when exploring the mechanisms that govern the beating rate and rhythm of the sinoatrial node (SAN), the heart’s primary pacemaker. SAN beating rate changes on a beat-to-beat basis. However, to date, there are no standard methods and tools for beating rate variability (BRV) analysis from electrograms (EGM) collected from different mammals and there is no centralized public database with such recordings. Methods: We used EGM recordings obtained from control SAN tissues of rabbits (n=9) and mice (n=30) and from mouse SAN tissues (n=6) that were exposed to drug intervention. The data were harnessed to develop a beat detector to derive the beat-to-beat interval time series from EGM recordings. We adapted BRV measures from heart rate variability and reported their range for rabbit and mouse. Results: The beat detector algorithm performed with 99% accuracy, sensitivity, and positive predictive value on the test (mouse) and validation (rabbit and mouse) sets. Differences in the frequency band cutoff were found between BRV of SAN tissue vs. HRV of in vivo recordings. A significant reduction in power spectrum density existed in the high frequency band and a relative increase was seen in the low and very low frequency bands. In isolated SAN, the larger animal had a slower beating rate, but with lower BRV, which contrasted the phenomena reported for in vivo analysis. Thus, the non-linear inverse relationship between the average HR and HRV is not maintained under in situ conditions. The beat detector, BRV measures and databases were contributed to the open-source PhysioZoo software (available at: https://physiozoo.com/). Conclusion: Our approach will enable standardization and reproducibility of BRV analysis in mammals. Different trends were found between beating rate and BRV or HRV in isolated SAN tissue versus recordings collected under in vivo conditions, respectively, implying a complex interaction between the SAN and the autonomic nervous system in determining HRV in vivo.